Islet adaptive changes to fructose-induced insulin resistance: β-cell mass, glucokinase, glucose metabolism, and insulin secretion - Maiztegui, Barbara (2009)
β-Cell mass, hexokinase/glucokinase (HK/GK) activity, glucose metabolism and insulin secretion were studied in the islets of rats with fructose-induced insulin resistance (IR). Normal male Wistar rats were fed a standard commercial diet and water without (control, C) or with 10% fructose-rich diet (FRD) for 3 weeks. Blood glucose (strips), triglyceride (commercial kit), and insulin (RIA) levels were measured at the time of death. Glucose-induced insulin release, glucose metabolism (14CO2 and 3H2O production from d-[U-14C]- and d-[5-3H]-glucose) and HK/GK activity (G-6-P production), transcription (RT-PCR), protein expression (Western blot), and cellular compartmentalization were measured in isolated islets (collagenase digestion). FRD rats presented normoglycemia but impaired glucose tolerance, hypertriglyceridemia, hyperinsulinemia, and increased HOMA-IR index. In these rats, β-cell mass decreased significantly by 33%, with a 44% increase in the percentage of apoptotic cells. Glucose-induced insulin release and islet glucose metabolism were higher in FRD rats. While GK activity (total and cytosolic fraction) and protein expression were significantly higher in FRD islets, HK showed no change in any of these parameters. Our results demonstrate that the changes induced by dietary-induced IR upon β-cell function and mass are strongly conditional on the nutrient model used. In our model (intact animals with impaired glucose tolerance), GK activity increases through mechanisms previously shown only in vitro or under highly hyperglycemic conditions. Such an increase plays a pivotal role in the adaptive increased release of insulin in response to IR, even in the presence of marked β-cell mass reduction.